Characterization of cell death caused by diplodiatoxin and dipmatol, toxic metabolites of Stenocarpella maydis. (August 2015) - Masango, Mxolisi G.; Ellis, Charlotte E.; Botha, Christo J.
Abstract: Diplodiosis, a neuromycotoxicosis of cattle and sheep grazing on mouldy cobs infected by Stenocarpella maydis, is considered the last major veterinary mycotoxicosis for which the causative mycotoxin is still unknown. The current study was aimed at characterizing the cell death observed in mouse neuroblastoma (Neuro-2a), Chinese hamster ovary (CHO-K1) and Madin–Darby bovine kidney (MDBK) cell lines exposed to the S. maydis metabolites (i.e. diplodiatoxin and dipmatol) by investigating the roles of necrosis and apoptosis. Necrosis was investigated using the lactate dehydrogenase (LDH) leakage and propidium iodide (PI) flow cytometry assays and apoptosis was evaluated using the caspase-3/7 and Annexin V flow cytometry assays. In addition, transmission electron microscopy (TEM) was used to correlate the cell death pathways observed in this study with their typical morphologies. Both diplodiatoxin and dipmatol (750 μM) induced necrosis and caspase-dependent apoptosis in Neuro-2a, CHO-K1 and MDBK cells. Ultrastructurally, the two mycotoxins induced mitochondrial damage, cytoplasmic vacuolation and nuclear fragmentation in the three cell lines. These findings have laid a foundation for future studies aimed at elucidating in detail the mechanism of action of the S. maydis metabolites. Highlights: Diplodiatoxin and dipmatol induced necrosis in Neuro-2a, CHO-K1 and MDBK cells. Diplodiatoxin and dipmatol induced caspase-dependent apoptosis in vitro . Mitochondrial damage, cytoplasmic vacuoles and nuclear fragmentation were observed.